Impact of Small and Medium Scale Enterprises (SMEs) Financing on Poverty Reduction in Nigeria - Rikwentishe Rimamnde; Danjuma Tsintop Ussaini; Samuel Mbah Adamu (Darul Yasin Al Sys, 2026)
Although financing for small and medium-scale enterprises (SMEs) is widely regarded as a mechanism for promoting inclusive development, empirical evidence on its contribution to poverty reduction in Nigeria remains mixed. This study examines the impact of SMEs financing on poverty reduction in Nigeria using time-series secondary data spanning 1992 to 2023. To ensure the reliability of the estimates, the data were first tested for stationarity using the Augmented Dickey-Fuller (ADF) unit root test. The study further employed the Autoregressive Distributed Lag (ARDL) bounds testing approach to examine the long-run relationship and the effects of Deposit Money Banks’ (DMBs) financing to SMEs, agricultural businesses, and manufacturing businesses on poverty reduction. The ARDL bounds test confirmed the existence of a long-run relationship between SMEs financing and poverty reduction in Nigeria. The long-run ARDL estimates showed that financing to SMEs exerted a negative but statistically insignificant effect on poverty reduction. In contrast, DMB financing to agricultural and manufacturing businesses had a positive and statistically significant effect on poverty reduction. The study concludes that although general SME financing has not significantly reduced poverty, targeted financing to the agricultural and manufacturing sectors has greater potential to improve poverty outcomes in Nigeria. These findings contribute to the understanding of sector-specific financial interventions and imply that strengthening credit-information infrastructure, expanding credit guarantees, prioritizing lending to productive sectors, maintaining single-digit interest rates, and improving the efficiency of financial delivery systems are essential for enhancing the poverty-reduction impact of bank financing.